2022
DOI: 10.1096/fasebj.2022.36.s1.0r750
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Pubertal Testosterone Implants Induce Hypertension in Female‐to‐Male Trans‐Sex Rat Model

Abstract: Introduction Androgens induce increases in blood pressure (BP) and risk of cardiovascular diseases (CVDs) in females, as seen in polycystic ovary syndrome females. However, it is not clear whether treatment with gender‐affirming hormone therapy in trans‐men have an impact on their BP or risk of CVD. Therefore, the present study was undertaken to test the hypothesis that chronic androgen supplements (starting post pubertal) in a rodent model of transgender men, will increase BP and promote metabolic dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In contrast, DHT treatment initiated in female Sprague-Dawley rats at 5 weeks of age resulted in elevated mean arterial pressure by 12 weeks of treatment [28]. The difference in initiation time is most likely not the reason for this discrepancy, as a study by the same group starting DHT post-puberty at 7 weeks of age also showed an increase in blood pressure [29]. Therefore, the discrepancy in blood pressure response between the current study and previous studies in rats could be due to either differences in treatment time or species differences in steroid metabolism [30].…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, DHT treatment initiated in female Sprague-Dawley rats at 5 weeks of age resulted in elevated mean arterial pressure by 12 weeks of treatment [28]. The difference in initiation time is most likely not the reason for this discrepancy, as a study by the same group starting DHT post-puberty at 7 weeks of age also showed an increase in blood pressure [29]. Therefore, the discrepancy in blood pressure response between the current study and previous studies in rats could be due to either differences in treatment time or species differences in steroid metabolism [30].…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, DHT treatment initiated in female Sprague–Dawley rats at 5 weeks of age resulted in elevated mean arterial pressure by 12 weeks of treatment [ 43 ]. The difference in initiation time is most likely not the reason for this discrepancy, as a study by the same group starting DHT post-puberty at 7 weeks of age also showed an increase in blood pressure [ 44 ]. Therefore, the discrepancy in blood pressure response between the current study and previous studies in rats could be due to either differences in treatment time or species differences in steroid metabolism [ 45 ].…”
Section: Discussionmentioning
confidence: 99%